2011
DOI: 10.1186/1471-2407-11-445
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal aberrations and aneuploidy in oral potentially malignant lesions: distinctive features for tongue

Abstract: BackgroundThe mucosae of the oral cavity are different at the histological level but appear all equally exposed to common genotoxic agents. As a result of this exposure, changes in the mucosal epithelia may develop giving rise to Oral Potentially Malignant Lesions (OPMLs), which with time may in turn progress to Oral Squamous Cell Carcinomas (OSCCs). Therefore, much effort should be devoted to identify features able to predict the likeliness of progression associated with an OPML. Such features may be helpful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
4
24
0
Order By: Relevance
“…The second surrogate endpoint was based on the subsite of the OPMDs considering that the tongue and FOM subsites were qualified predictors of risk of cancer development in a recent study involving a prospective cohort of 296 patients with OPMDs with mild/moderate dysplasia (17,57,58). Distinctive features of chromosomal aberrations and increased incidence of DNA aneuploidy for the tongue OPMDs with respect to the OPMDs in all the other oral subsites were also reported in a recent study from our group, which suggested that these patients should receive a distinctive special attention (15).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The second surrogate endpoint was based on the subsite of the OPMDs considering that the tongue and FOM subsites were qualified predictors of risk of cancer development in a recent study involving a prospective cohort of 296 patients with OPMDs with mild/moderate dysplasia (17,57,58). Distinctive features of chromosomal aberrations and increased incidence of DNA aneuploidy for the tongue OPMDs with respect to the OPMDs in all the other oral subsites were also reported in a recent study from our group, which suggested that these patients should receive a distinctive special attention (15).…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, OPMDs are not the only precursors of OSCCs (2-6, 52) because OSCCs may also develop from ONAMFs characterized by absence of dysplasia and with a transformation rate that still remains to be evaluated. The genomic characteristics of ONAMFs and OPMDs were recently investigated using array-comparative genomic hybridization and hr-DNA-FCM in a small number of cases (15,16). Presently, 135 ONAMFs and 195 OPMDs (171 nondysplastic and 24 dysplastic) for a consecutive series of 165 patients with OMPD were investigated by hr-DNA-FCM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study was undertaken within the frame of a wider project carried on over the last 6 years and aiming to assess the DNA‐aneuploidy point prevalence and role among oral potentially malignant disorders and SCC using fresh/frozen samples coupled with high‐resolution and high‐sensitivity DNA‐FCM (Pentenero et al , , ,b, ; Donadini et al , ; Castagnola et al , ; Giaretti et al , ,b, ). The preparation of the nuclei suspension from fresh/frozen material and DAPI staining allowed us to routinely obtain G0/G1 DNA diploid control nuclei with CV values as low as 1% and an extremely low background, thus allowing the detection of DNA near‐diploid aneuploid sublines with DNA changes as low as 2.5% with respect to the DNA diploid status (Donadini et al , ).…”
Section: Discussionmentioning
confidence: 99%